The Imperial Eagle in the South-east of Kazakhstan 2022–2023: Distribution, Population Numbers, Threats - Alyona G. Kaptyonkina; Genriyetta I. Pulikova; Nurum A. Sagaliev; Igor V. Karyakin (Пернатые хищники и их охрана)
The Imperial Eagle (Aquila heliaca) is one of the rare species of eagles breeding in Kazakhstan and inhabiting almost the entire territory of the country. The south and south-east of Kazakhstan is the south-eastern border of the breeding range of the species (Karyakin, 2020). It is this part of the range that will be considered in this paper.